A Highly Sensitive Ag/MG-CQDs/ZnO NP Ultraviolet Photodetector - Kumar A.; Gupta P.K.; Srivastava M.; Pandey A.; Srivastava A.; Srivastava S.K. (My University, 2025)
This article reports the fabrication of marigold flower-derived carbon quantum dots (MG-CQDs) and ZnO nanoparticle (NP)-layered thin-film-based ultraviolet (UV) photodetector (PD) on Si/SiO2 substrates. The MG-CQDs have been green synthesized from natural biomass marigold (MG) flowers by a facile, low-cost hydrothermal synthesis method. The ZnO NPs have been prepared through a rapid sol-gel process. The Ag/MG-CQDs/ZnO NP-layered thin-film-based fabricated UV PDs have good responsivity ({R} ), external quantum efficiency (EQE), and detectivity ({D}{ast } ) values 42.78 A/W, 14535.54%, and {1.99}times {10}{{13}} jones, respectively, under UV radiation (365 nm). The response time of Ag/MG-CQDs/ZnO NP-fabricated UV PD shows adequate rise time (0.213 s) and fall time (0.085 s). © 2001-2012 IEEE.